Incidence and outcome of SARS‐CoV‐2 infection on solid organ transplantation recipients: A nationwide population‐based study. Issue 7 (20th January 2021) - Trapani, Silvia; Masiero, Lucia; Puoti, Francesca; Rota, Maria C.; Del Manso, Martina; Lombardini, Letizia; Riccardo, Flavia; Amoroso, Antonio; Pezzotti, Patrizio; Grossi, Paolo A.; Brusaferro, Silvio; Cardillo, Massimo; et al.
Abstract: Since February 21 2020, when the Italian National Institute of Health (Istituto Superiore di Sanità–ISS) reported the first autochthonous case of infection, a dedicated surveillance system for SARS‐CoV‐2‐positive (COVID+) cases has been created in Italy. These data were cross‐referenced with those inside the Information Transplant System in order to assess the cumulative incidence (CI) and the outcome of SARS‐COV‐2 infection in solid organ transplant recipients (SOTRs) who are assumed to be most at risk. We compared our results with those of COVID+ nontransplanted patients (Non‐SOTRs) with follow‐up through September 30, 2020. The CI of SARS‐CoV‐2 infection in SOTRs was 1.02%, higher than in COVID+ Non‐SOTRs (0.4%, p < .05) with a greater risk in the Lombardy region (2.89%). The CI by type of organ transplant was higher for heart (CI 1.57%, incidence rate ratio [IRR] 1.36) and lower for liver (CI 0.63%, IRR 0.54). The 60‐day CI of mortality was 30.6%, twice as much that of COVID+ Non‐SOTRs (15.4%) with a 60‐day gender and age adjusted odds ratio (adjusted‐OR) of 3.83 for COVID+ SOTRs (95% confidence interval [3.03–4.85]). The lowest 60‐day adjusted‐OR was observed in liver SOTRs (OR 0.46, 95% confidence interval [0.25–0.86]). More detailed studies on disease management and evolution will be necessary in these patients at greater risk of COVID‐19. Abstract : In Italy, SARS‐CoV‐2 infection risk for solid organ recipients compared to the general population is two times higher and mortality risk is four times higher, with heart recipients at the highest risk of infection and liver recipients at the lowest risk of both infection and mortality.